Impact of maternal nutrition in viral infections during pregnancy - Mate, Alfonso; Reyes-Goya, Claudia; Santana-Garrido, Álvaro; Sobrevia, Luis [UNESP]; Vázquez, Carmen M. (Elsevier, 2021)
Other than being a physiological process, pregnancy is a condition characterized by major adaptations of maternal endocrine and metabolic homeostasis that are necessary to accommodate the fetoplacental unit. Unfortunately, all these systemic, cellular, and molecular changes in maternal physiology also make the mother and the fetus more prone to adverse outcomes, including numerous alterations arising from viral infections. Common infections during pregnancy that have long been recognized as congenitally and perinatally transmissible to newborns include toxoplasmosis, rubella, cytomegalovirus, and herpes simplex viruses (originally coined as ToRCH infections). In addition, enterovirus, parvovirus B19, hepatitis virus, varicella-zoster virus, human immunodeficiency virus, Zika and Dengue virus, and, more recently, coronavirus infections including Middle Eastern respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS) infections (especially the novel SARS-CoV-2 responsible for the ongoing COVID-19 pandemic), constitute relevant targets for current research on maternal-fetal interactions in viral infections during pregnancy. Appropriate maternal education from preconception to the early postnatal period is crucial to promote healthy pregnancies in general and to prevent and/or reduce the impact of viral infections in particular. Specifically, an adequate lifestyle based on proper nutrition plans and feeding interventions, whenever possible, might be crucial to reduce the risk of virus-related gestational diseases and accompanying complications in later life. Here we aim to provide an overview of the emerging literature addressing the impact of nutrition in the context of potentially harmful viral infections during pregnancy.
Keywords: Feeding interventions; Fetal programming; Food insecurity; Microbiota; Mother-to-child transmission; Pregnancy and viral infections